Fenomena Keislaman Sebagai Gejala Budaya dan Sosial - Sifa Nurwahida (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2025)
This article aims to examine the influence of the presence of Islam on the social and cultural aspects of society, as well as to explain the role of Islamic teachings in shaping and transforming the social order. The discussion focuses on how Islamic teachings, particularly those derived from the Qur’an, are understood and implemented by Muslims within a dynamic socio-cultural reality. This study employs a qualitative method with a literature review approach through a comprehensive analysis of relevant sources in the field of philosophical Islamic studies. This approach is used to explore the relationship between normative Islamic teachings and the social construction of society. The findings indicate that the teachings and commands of the Qur’an, as practiced by Muslims, have a significant influence on the formation of values, patterns of interaction, and the social and cultural structures of society. In Indonesia, Islam has developed through processes of dialogue and acculturation with local cultures without diminishing the substance of its normative teachings. This is evident in the religious practices of Javanese and Malay communities, as well as in the marpangir tradition among the Batak Angkola people, which has undergone a process of value reinterpretation in accordance with the principle of tawhid. This study affirms that Islam functions not only as a system of belief but also as a social force capable of shaping cultural order and promoting social change oriented toward the values of justice, public welfare, and social harmony. Through a contextual and inclusive approach, Islam can be presented as a religion that is adaptive to socio-cultural change while maintaining its normative foundations.